Meanings of victory in the Holy Qur’an and its causes - Odeh, Ibrahim Hammad Yousef (Journal of Islamic Sciences, 2024)
Victory came in the Holy Qur’an with different words and meanings like success and victory, It is divided into two types: victory in this worldly life and victory after death, As for the reasons for victory, they are also of two types. Either the material one depends on the laws of the universe and science, If we take it, we will win and advance, There is a moral aspect to mobilizing people spiritually to be prepared for victory, patience and fearlessnessAs for the believers abandoning their work and relying on the coming of victory from God alone without taking into account the reasons, this is a defect in understanding the Qur’anic text, and using resources for victory God’s intervention does not mean sending angels to fight instead of Muslims, but rather Muslims must fully prepare and fightThis research aims to reveal the meanings of victory and similar words, It also aims to prove that victory in the Holy Qur’an has reasons and laws that must be followed. And God helps His servants if they work hard to achieve victory, not without work, The researcher used the descriptive analytical method, where the focus was on describing the victory and its meanings and mentioning the reasons for the victory and its methods, The study came out with results, the most important of which is that victory in all its meanings means victory in the end of a matter or thing, Therefore, its causes are worldly, and God created the mind for man so that he can use it, advance with it, and achieve victory.
Keywords: The Holy Quran; Victory; Factors of victory; Divine laws